Micro-Technologies for Assessing Microbial Dynamics in Controlled Environments - Davidson, Shanna-Leigh; Niepa, Tagbo H. R. (Frontiers in Microbiology, 2022)
“Microbial Dark Matter” describes the expansive list of microorganisms that remain elusive to traditional lab culturing techniques, such as agar plates and flasks. With recent advances in microfabrication technologies, the miniaturization of traditional culturing techniques has provided ideal methods for interrogating microbial communities in a confined and finely controlled environment. Micro-technologies offer high-throughput screening and analysis, reduced experimental time and resources, and are low footprint. More importantly, they provide access to culturing microbes in situ in their natural environments and similarly, offer optical access to real-time dynamics under a microscope. Utilizing micro-technologies for culturing the “unculturable” will propel many fields forward: drug discovery, point-of-care diagnostics, and fundamental studies in microbial community behaviors rely on the exploration of novel metabolic pathways. However, micro-technologies are still largely proof-of-concept, and scalability and commercialization of micro-technologies will require increased accessibility to expensive equipment and resources, as well as simpler designs for usability. Here, we discuss three different technologies for miniaturized culturing practices, including microarrays, micromachined devices, and microfluidics, advancements to the field as well as perceived challenges.